Avaliação de aderência de práticas do agile testing em times que utilizam scrum - Cole, Aniela (Universidade do Vale do Rio dos Sinos, 2015)
Based on studies of agility, Scrum and Agile Testing have been identified specific aspects of testing in agile environments, including types and test techniques that should be performed by an agile team, as well as its form of more efficient execution. Based on this survey, it has been developed a case study on a company's information technology sector, with the objective of mapping the testing types and techniques which are used by this company. From the analysis it was possible to identify which types and testing techniques are being performed as suggested by the practice Agile Testing and what can be improved. This article aims to evaluate the adherence of a company team in question in relation to the practice Agile Testing.
Keywords: Agilidade; Scrum; Integração contínua; Testes de software; Agile testing